Femmes en revolte: a propos de la dialectique du maitre et de l’esclave chez Simon de Beauvoir - Vuillerod, Jean-Baptiste (B@belonline, 2022)
This article aims to discuss how Simone de Beauvoir uses Hegel’s master-slave dialectic to describe the men-women relationship in our societies. Unlike the contemporary readings that insist on the voluntary servitude of women in Beauvoir’s Second sex, I emphasize the role of political struggles and the importance of friendship between women and sorority in the Beauvoirian critique of masculine domination. I argue that the resistance of women against patriarchy is not a blind spot in the Second Sex but is a central core in Beauvoir’s conception of feminism, and I defend the idea that her reading of Hegel’s dialectic is at work here.